Evaluation of collagen/hydroxyapatite electrospun layers loaded with vancomycin, gentamicin and their combination: Comparison of release kinetics, antimicrobial activity and cytocompatibility - Suchý, Tomáš; Šupová, Monika; Sauerová, Pavla; Hubálek Kalbáčová, Marie; Klapková, Eva; Pokorný, Marek; Horný, Lukáš; Závora, Jan; Ballay, Rastislav; Denk, František; Sojka, Martin; Vištejnová, Lucie (European journal of pharmaceutics and biopharmaceutics, 2019)
The aim of this study was to develop a biodegradable nanostructured electrospun layer based on collagen (COL), hydroxyapatite nanoparticles (HA), vancomycin hydrochloride (V), gentamicin sulphate (G) and their combination (VG) for the treatment of prosthetic joint infections and the prevention of infection during the joint replacement procedure. COL/HA layers containing different amounts of HA (0, 5 and 15 wt%) were tested for the in vitro release kinetics of antibiotics, antimicrobial activity against MRSA, gentamicin-resistant Staphylococcus epidermidis and Enterococcus faecalis isolates and cytocompatibility using SAOS-2 bone-like cells. The results revealed that the COL/HA layers released high concentrations of vancomycin and gentamicin for 21 days and performed effectively against the tested clinically-relevant bacterial isolates. The presence of HA in the collagen layers was found not to affect the release kinetics of the vancomycin from the layers loaded only with vancomycin or its combination with gentamicin. Conversely, the presence of HA slowed down the release of gentamicin from the COL/HA layers loaded with gentamicin and its combination with vancomycin. The combination of both antibiotics exerted a positive effect on the prolongation of the conversion of vancomycin into its degradation products. All the layers tested with different antibiotics exhibited potential antibacterial activity with respect to both the tested staphylococci isolates and enterococci. The complemental effect of vancomycin was determined against both gentamicin-resistant Staphylococcus epidermidis and Enterococcus faecalis in contrast to the application of gentamicin as a single agent. This combination was also found to be more effective against MRSA than is vancomycin as a single agent. Importantly, this combination of vancomycin and gentamicin in the COL/HA layers exhibited sufficient cytocompatibility to SAOS-2, which was independent of the HA content. Conversely, only gentamicin caused the death of SAOS-2 independently of HA content and only vancomycin stimulated SAOS-2 behaviour with an increased concentration of HA in the COL/HA layers. In conclusion, COL/HA layers with 15 wt% of HA impregnated with vancomycin or with a combination of vancomycin and gentamicin offer a promising treatment approach and the potential to prevent infection during the joint replacement procedures.
Keywords: Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; Microbial Sensitivity Tests; Enterococcus faecalis; mikrobiální testy citlivosti; gentamiciny; synergismus léků; kostní cementy; kinetika; Kinetics; Cell Line; antibakteriální látky; Durapatite; hydroxyapatit; methicilin rezistentní Staphylococcus aureus; Staphylococcus epidermidis; kolagen; Drug Synergism; Humans; Gentamicins; Vancomycin; Prosthesis-Related Infections; infekce spojené s protézou; vankomycin; lidé; Bone Cements; Collagen; buněčné linie